SIMULATIONS AND ANALYSIS OF COVID-19 AS A FRACTIONAL MODEL WITH DIFFERENT KERNELS - Yao, Shao-wen; Farman, Muhammad; Akgul, Ali; Nisar, Kottakkaran Sooppy; Amin, Maryam; Saleem, Muhammad Umer; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2023)
Recently, Atangana proposed new operators by combining fractional and fractal calculus. These recently proposed operators, referred to as fractal-fractional operators, have been widely used to study complex dynamics. In this paper, the COVID-19 model is considered via Atangana-Baleanu fractal-fractional operator. The Lyapunov stability for the model is derived for first and second derivative. Numerical results have developed through Lagrangian-piecewise interpolation for the different fractal-fractional operators. We develop numerical outcomes through different differential and integral fractional operators like power-law, exponential law, and Mittag-Leffler kernel. To get a better outcome of the proposed scheme, numerical simulation is made with different kernels having the memory effects with fractional parameters.
Keywords: COVID-19 Model; Stability; Power-Law; Exponential Law; Mittag-Leffler; Fractional Parameters